Experimental determination of the effects of pretreatment on selected Nigerian lignocellulosic biomass in bioethanol production - Adeolu A. Awoyale; David Lokhat (Scientific Reports, 2021)
Abstract In the present study, five lignocellulosic biomass namely, corn cobs (Zea mays), rice husks (Oryza sativa), cassava peels (Manihot esculenta), sugar cane bagasse (Saccharum officinarum), and white yam peels (Dioscorea rotundata) of two mesh sizes of 300 and 425 microns and a combination of some and all of the biomass were pretreated using combined hydrothermal and acid-based, combined hydrothermal and alkali-based and hydrothermal only processes. The raw and pretreated biomass were also characterized by Fourier transform infrared spectroscopy (FT-IR), Brunauer–Emmett–Teller (BET), X-Ray diffraction (XRD), and Scanning electron microscopy (SEM) to determine the effects of the various pretreatments on the biomass being studied. The cellulose values of the raw biomass range from 25.8 wt% for cassava peels biomass to 40.0 wt% for sugar cane bagasse. The values of the cellulose content increased slightly with the pretreatment, ranging from 33.2 to 43.8 wt%. The results of the analysis indicate that the hydrothermal and alkaline-based pretreatment shows more severity on the different biomass being studied as seen from the pore characteristics results of corn cobs + rice husks biomass, which also shows that the combination of feedstocks can effectively improve the properties of the biomass in the bioethanol production process. The FTIR analysis also showed that the crystalline cellulose present in all the biomass was converted to the amorphous form after the pretreatment processes. The pore characteristics for mixed corn cobs and rice husks biomass have the highest specific surface area and pore volume of 1837 m2/g and 0.5570 cc/g respectively.